Utilização de reações foto-Fenton na prevenção de contaminações agrícolas - Trovó, Alam Gustavo [UNESP]; Dalla Villa, Ricardo [UNESP]; Nogueira, Raquel Fernandes Pupo [UNESP] (Sociedade Brasileira de Química, 2005)
In this work the application of the photo-Fenton process for the treatment of washing water of herbicide containers using solar energy was studied. The influence of the H2O2 concentration and the iron source on the degradation of tebuthiuron and diuron was investigated. The degradation efficiency was strongly affected by the iron source. Using ferrioxalate, total mineralization of diuron and tebuthiuron was obtained either for the individual compounds or for a mixture containing both herbicides, while when using Fe(NO3)3, the maximum mineralization reached for both herbicides was only 50%.
Use of photo-Fenton reactions in the prevention of agricultural contaminations
Keywords: ferrioxalate; herbicides; solar